Employment-Poverty Linkages and Policies: The Case of Bolivia - Luis Carlos Jemio; Maria del Carmen Choque (Institute for Advanced Development Studies (INESAD), 2003)
This study focuses on analysing the linkages between output growth, employment and poverty, at both the macro and micro levels. At the macro level, the linkage between poverty and output growth is conceptualised in terms of the average productivity of the employed work force, which in turn gets reflected in low levels of real wages and low levels of earnings in self-employment. At the micro level of a household, the same linkage between poverty and employment operates through the type and productivity of economic activities in which the earning members of a household are engaged, the low level of human capital of the members of the workforce, the dependency burden that limits participation in the workforce, and the availability of remunerative employment.
Keywords: J24; O54; o17; 330; Employment; Poverty; Growth; Bolivia